Letramento e educação inclusiva : construindo práticas de leitura e escrita no ensino fundamental II - Menezes, Maria Aparecida Alves (2015)
This research report aims to present the application of a didactic sequence with the genre cooking recipe in a class of 6th grade Elementary School a center of specialized education of Salvador - BA. It aims to investigate the gender contribution to the expansion of skills and communication skills and literacy of students, in their different functions and purposes. We use the methodology of action research, qualitative and interpretative nature and interventional approach. This research is guided by the theoretical assumptions of Galvão Filho (2009), Sassaki (1997; 2005a; 2005b) regarding inclusive education. For the concepts of literacy, reading, writing and genre were utilized Soares studies (2004; 2010), Kleiman (1995; 2001), Marcuschi (2002; 2005; 2008) and National Curriculum Standards of Portuguese Language Teaching Elementary School (1998), among others. The results reveal that the language teaching using the genre is configured as the body in access to linguistic knowledge necessary for effective socio-cultural activities and expansion of the literacy process of the students.